Does the SDR System Generate Permanent Resource Transfers? - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
The paper analyzes whether the SDR system generates permanent resource transfers-i.e., transfers of resources that do not involve equivalent quid pro quos. It is argued that SDR allocation only gives rise to permanent resource transfers if the SDR interest rate is uncompetitive or if holding SDRs is perceived to be risky, and that the use of SDRs gives rise to permanent resource transfers only if the SDR interest rate is uncompetitive. These conclusions are reconciled with the fact that SDR allocation can provide reserves to many countries at terms more favorable than the costs of borrowing or earning reserves.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet